2021
DOI: 10.3168/jds.2020-20104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spray-dried bovine plasma protein in milk replacers fed at a high plane of nutrition on performance, intestinal permeability, and morbidity of Holstein calves

Abstract: Spray-dried plasma protein (SDP) has been shown to improve growth and intestinal function in young calves when included in milk replacers (MR) fed at conventional rates. Use of an SDP and wheat protein blend to replace a portion of whey protein has been shown to perform similarly to using an all-whey protein control MR. However, a trend in the dairy industry is to feed calves for greater rates of growth during the preweaning period. The purpose of this study was to determine the effects of increasing amounts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We detected the contents of serum DAO and D-LA in piglets, which reflect the integrity of and the degree of damage to the intestinal barrier [ 26 , 27 ]. The results showed that the levels of serum DAO and D-LA in the 7S and 11S groups were significantly higher than those in the control group ( p < 0.05; Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…We detected the contents of serum DAO and D-LA in piglets, which reflect the integrity of and the degree of damage to the intestinal barrier [ 26 , 27 ]. The results showed that the levels of serum DAO and D-LA in the 7S and 11S groups were significantly higher than those in the control group ( p < 0.05; Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…D-lactic acid (D-LA) is an indicator of bacterial metabolites and bacterial lysis. The content of D-LA increases in serum with increased intestinal mucosal permeability [ 39 ]. DAO is a highly active intracellular enzyme that is a reliable serum marker for the indirect assessment of the mucosal epithelial cell layer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…With manual high milk feeding programs, providing at least 2 weekly steps down in amounts offered will smooth out the weaning transition. 27 Providing ad libitum access to forage, especially alfalfa, should be avoided as it may decrease starter intake. As mentioned earlier, forage is poorly digested in the young rumen and contributes very little to nutrient supply.…”
Section: The Weaning Transitionmentioning
confidence: 99%